Perkembangan Sektor Industri Manufaktur Terhadap Globalisasi - Muhammad Syahrul Maulana; Alif Finno Fidzaky; Ayunda Febri Kinanti; Dimas Prayoga; Muhammad Yasin (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
In the development of the world, the manufacturing industry sector continues to develop every year, this results in increased competition in the business world, especially in the economic sector. Therefore, every country is required to be more advanced and developed so that the welfare of the population is evenly guaranteed. In the business world, if the business is growing, the competition between one company and another will increase tighter. To be able to compete with other companies, the company must be able to manage all assets owned and its obligations as much as possible so that the operational activities of the company can run well according to the original plan for the company to be established.